Quelle place pour les masculinités dans la spiritualité béguinale ? Penser les béguins au regard des études de genre - Claire Donnat-Aracil (Perspectives Médiévales)
While it is common to consider Beguine spirituality as predominantly, if not exclusively, feminine, several literary texts written in the oïl language during the 13th century offer the possibility of a different perspective, designating members of Beguinages using the masculine forms beguins or the inclusive doublet beguins et beguines. Given that the grammatical masculine can hardly, in the latter case, be read as anything other than a specific masculine, this article aims to show that, in 13th-century northern France, the assimilation of Beguine productions to texts reserved for women is not always as self-evident as one might think. By successively analyzing sermons intended for Beguine communities, pious poetry directly from these communities, and an epideictic text firmly opposed to them, this article aims, on the one hand, to highlight the possibility of a masculine reading of this spirituality, and to show, on the other hand, that the gender stereotypes conveyed by certain clerics in the 13th century have contributed, from the Middle Ages to the present day, to rendering invisible the possible presence of men within Beguine communities.